THE EFEKTIFITAS ALOKASI WAKTU PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM KURIKULUM MERDEKA DI SDN NEUSOK TEUBALUI - Halimah, Siti; Muluk, Safrul; Silahuddin (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2024)
This study aims to evaluate the effectiveness of Islamic Religious Education (PAI) learning time allocation in Merdeka Curriculum at SDN Neusok Teubalui. Using a qualitative approach with observation, interview, and documentation methods, this study found that the allocation of 3 hours of PAI intracurricular time per week is running well. However, co-curricular learning (1 hour for the Pancasila Student Profile Strengthening Project or P5) is considered less effective. Time constraints, lack of collaboration between PAI teachers and class teachers, and the often neglected time allocation for P5 are the main obstacles. Some teachers only utilize co-curricular hours for reading, without integrating relevant themes. To overcome this problem, it is suggested that there should be better coordination in the implementation of P5, including the appointment of activity coordinators based on the learning phase. This study underlines the importance of optimizing learning time and collaboration between educators to improve the effectiveness of PAI learning in shaping students' character in accordance with the values of Pancasila.